Malignant phyllodes tumor of the breast with heterologous high-grade angiosarcoma - Ghassan Tranesh; Aziza Nassar (Elsevier, 2017)
Phyllodes tumors (PTs) account for <3% of fibroepithelial breast lesions and for 0.3% to 1.0% of primary breast tumors. They occur predominantly in middle-aged women (mean age range, 40-50 years). PTs can be categorized into benign, borderline, and malignant; the first 2 categories are distinguished only by degree of cellular atypia and mitotic activity. Malignant PTs are more frequent among persons of Hispanic ethnicity, especially those born in Central America or South America. Heterologous sarcomatous elements may be present in malignant PTs, predominantly liposarcoma and rarely fibrosarcoma, rhabdomyosarcoma, leiomyosarcoma, osteosarcoma, and chondrosarcoma. Breast angiosarcoma (BA) is a rare heterologous, sarcomatous element that may arise secondary to malignant PT. We report a 47-year-old woman with no history of previous surgery or radiation therapy who presented to the emergency department with a painful right breast mass. She admittedly noticed the right breast mass for many years; however, recently it increased in size. Mammography and ultrasonography identified a partially cystic mass. Core needle biopsy showed dense hyalinized fibrous tissue with old blood clots, suggestive of infarcted fibroadenoma. The patient received antibiotics and analgesics; however, she reported intractable pain and a worsening skin rash of her right breast. Chest computed tomography and magnetic resonance imaging showed a doubling in mass size, with pectoralis major muscle involvement. Incisional biopsy showed malignant PT with heterologous high-grade angiosarcoma. The diagnosis of angiosarcoma was confirmed through immunoreactivity for CD31, FLI1, and ERG immunostains. Keywords: Angiosarcoma, Breast, High grade angiosarcoma, Phyllodes tumor